The models of Relationship between Center of Gravity of Human and Weight, Height and 3 Body’s Indicators (Chest, Waist and Hip) - Vu, Tran Anh; Huy, Hoang Quang; Tu, Nguyen Anh; Tuan, Le Van; Khanh, Le Viet; Huong, Pham Thi Viet (Old Journal, 2019)
Determining the position of the Center of Gravity (CoG) of the human body takes an important role in human movement analysis. Recently, there are several measurement methods to estimate the center of body point. These methods are generally costly, time consuming and complicated implementation process. In this paper, we propose a simple model that can determine the body’s Center of Mass through body indicators: height, weight and three other parameters of body’s measurement (sizes of Chest, Waist and Hip). From the measured data, a quick, stable and accurate model has been built, which reveals the relationship between the Center of Gravity (CoG) and the body indicators: weight, height and body measurements.